Pareuchiloglanis hupingshanensis, a new species of the glyptosternine catfish (Siluriformes: Sisoridae) from the middle Yangtze River, China - Kang, Zujie; Chen, Yongxia; He, Dekui (Zootaxa, 2016)
A new glyptosterniod catfish, Pareuchiloglanis hupingshanensis, is described on the basis of 29 specimens, which were collected from Hunan Hupingshan National Nature Reserve (HHNNR) in the Yangtze River basin, China. It can be distinguished from all congeners by morphology and sequences of the cytochrome b gene. Morphometric and molecular data show that the new species is closely related to P. sinensis Hora et Silas but differs from it in possessing a premaxillary tooth band with a deeper median indentation; a dentary tooth band which consists of two shorter and wider patches; a lower angle of gill opening, opposite to the base of the 4th or 5th (vs. second or third) branched pectoral-fin ray; an upper lip edged with dense papillae; the posterior end of the ventral fin falling distinctly short of (vs. almost reaching ) anus; a shorter dorsal fin; and a greater caudal-fin base depth.